High‐risk cytogenetic abnormalities in multiple myeloma: PETHEMA‐GEM experience - Veronica González‐Calle; Paula Rodriguez‐Otero; Maria J. Calasanz; Manuela Guijarro; Joaquin Martínez‐López; Laura Rosiñol; Miguel T. Hernández; Ana I. Teruel; Mercedes Gironella; Albert Oriol; Javier de laRubia; Ana P. González‐Rodríguez; et al. (HemaSphere)
Abstract This study examines the impact of cytogenetic abnormalities and their co‐segregation on the prognosis of newly diagnosed multiple myeloma patients. The analysis included 1304 patients from four different GEM‐PETHEMA clinical trials. Genetic alterations, such as t(4;14), t(14;16), del(17p), +1q, and del(1p), were investigated using FISH on CD38 purified plasma cells. The frequency of genetic alterations detected were as follows: del(17p) in 8%, t(4;14) in 12%, t(14;16) in 3%, +1q in 43%, and del(1p) in 8%. The median follow‐up was 61 months, and the median progression‐free survival (PFS) and overall survival (OS) were 44 months and not reached, respectively. Consistent with previous reports, the presence of t(4;14) was associated with shorter PFS and OS. In our series, the presence of t(14;16) did not impact survival, maybe due to limitations in sample size. Del(17p) was linked to poor prognosis using a cut‐off level of ≥20% positive cells, without any impact of higher cut‐off in prognosis, except for patients with clonal fraction ≥80% who had a dismal outcome. Cosegregation of cytogenetic abnormalities patients worsened the prognosis in t(4;14) patients but not in patients with del(17p), which retained its adverse prognosis even as a solitary abnormality. Gain(1q) was associated with significantly shorter PFS and OS, while del(1p) affected PFS but not OS. Nevertheless, when co‐segregation was eliminated, the detrimental effect of +1q or del(1p) was no longer observed. In conclusion, this study confirms the prognostic significance of high‐risk cytogenetic abnormalities in MM and highlights the importance of considering co‐occurrence for accurate prognosis assessment.